REGIME DE PROGRESSÃO CONTINUADA E AVALIAÇÃO EM UMA ESCOLA ESTADUAL NO MUNICÍPIO DE HUMAITÁ/AM (Revista Contexto & Educação, 2020)
The Education Guidelines and Bases Law (brasilian LDB) No. 9,394/96 provides in Article 32 §2° for school institutions to use the Continued Progression method, which is directly linked to evaluation. The research aims to demonstrate statistically and descriptively the reality of the evaluation in the respective method, showing issues such as learning time, evaluative practices and individual monitoring from the perspective of the students with whom a research was carried out in the 9th grade of Elementary School II, at a State School in the Humaitá - AM city. Studies on the theme made it possible to identify the rights provided by law that served as the basis for our analysis, demonstrating that all evaluative forms are used in the classroom, however, there are still things of traditional teaching in the measures used, with students who want to wait by instructions and that the term “disapproval” is still present in the school context, even if its use is prohibited.